High Precision Bone Cutting by Er: YAG Lasers Might Minimize the Invasiveness of Navigated Brain Biopsies - Ha, Thanh Tu; Thieringer, Florian M.; Bammerlin, Martin; Cordier, Dominik (Frontiers in Oncology, 2022)
Biopsies of brain tissue are sampled and examined to establish a diagnosis and to plan further treatment, e.g. for brain tumors. The neurosurgical procedure of sampling brain tissue for histologic examination is still a relatively invasive procedure that carries several disadvantages. The “proof of concept”-objective of this study is to answer the question if laser technology might be a potential tool to make brain biopsies less invasive, faster and safer. Laser technology might carry the opportunity to miniaturize the necessary burr hole and also to angulate the burr hole much more tangential in relation to the bone surface in order to take biopsies from brain regions that are usually only difficult and hazardous to access. We examined if it is possible to miniaturize the hole in the skull bone to such a high extent that potentially the laser-created canal itself may guide the biopsy needle with sufficient accuracy. The 2-dimensional, i.e. radial tolerance of the tip of biopsy needles inserted in these canals was measured under defined lateral loads which mimic mechanical forces applied by a surgeon. The canals through the skull bones were planned in angles of 90° (perpendicular) and 45° relative to the bone surface. We created a total of 33 holes with an Er:YAG laser in human skull bones. We could demonstrate that the achievable radial tolerance concerning the guidance of a biopsy needle by a laser created bone canal is within the range of the actual accuracy of a usual navigated device if the canal is at least 4 mm in length. Lateral mechanical loads applied to the biopsy needle had only minor impact on the measurable radial tolerance. Furthermore, in contrast to mechanical drilling systems, laser technology enables the creation of bone canals in pointed angles to the skull bone surface. The latter opens the perspective to sample biopsies in brain areas that are usually not or only hazardous to access.